Friedrich Schlegel e a forma da filosofia - Santos, Thiago das Chagas (Universidade Federal de São Carlos, 2011)
Friedrich Schlegel is inserted in the philosophical landscape know as German Idealism, precisely the reflection on the idea of system. Although his writings and reflections do not seem, at least to his contemporaries and first commentators, not appreciate the systematicity, careful consideration may show us that the issue is the definition of the idea of system. It this understanding is lacking in his contemporaries and critics of the nineteenth century. But what lies behind their efforts is the understanding that the very transcendental philosophy requires that the system design to be rethought. It is this effort translated into the statement that every system should be original an individual who can perform effectively and historically transcendental idealism. It is this requirement that binds directly to the question of form philosophy, an issue that we try to think here. One can not speak more in creating the system, but of creating a the individual system, for if the reason is one, it is expressed in various ways individuals. The totality is expressed in the idea that philosophy is a work in progress and collective, infinite progressiveness in constant exchange, in which efforts are individuals creations of individual systems, forming the same whole and the whole history of philosophy. If the form of philosophy is infinite which in itself contains an infinite number of beginnings, we can not expect to find a system that is above the individual, the individual genius of each. The harmonious unity of this requirement is developed on the plane of culture, in which all forms must be unified, and the individual level, which should now also be fully, man and philosopher, must be a philosophy that does not separate the life of the existence of philosopher.
Keywords: Estética; Forma (Filosofia); Romantismo alemão; CIENCIAS HUMANAS::FILOSOFIA